Analysis of Particulate Matter Composition - Daniela Durcanska (Communications - Scientific letters of the University of Zilina, 2010)
According to current research, particulate matter (PM) has a negative impact on citizens in particular (respiratory and cardiovascular diseases). Based on EU studies, deaths of 347,900 Europeans are attributable to air pollution. Formation of particulate matter from road transport has been a concern for big cities in particular.For long time monitoring PM we choosed the sections of roads located both within urban areas and rural areas were selected for longterm monitoring, differing in particular by the surface of the roadway – either with asphalt concrete paving (AC) or with stone mastic asphalt (SMA) paving, an asphalt compound with disintegrated stone grade and a higher percentage of asphalt binder.We were executed the Air Samples with using medium-volume LECKEL MVS6 sampling pump.